PRODUCER PERFORMANCE EVALUATION OF TELEVISION PROGRAM AT PT. PACIFIC TELEVISION MANADO - Pangemanan, Gerald Carol (Universitas Sam Ratulangi, 2014)
In the world of television broadcasting in particular, plays a very important producer in television production wheel rotation. The task of a producer is to lead the entire production team in accordance with the objectives set, both in terms of creative and production management in accordance with the agreed budget. So that, improving the producer performance is the one that determine the outcome of an event or television program itself. The purpose of this paper is to analyze producer performance evaluation of television program at PT. Pacific Television Manado. This research uses Descriptive type of research with Balance Scorecard Tools to measuring the performance and implementation of the performance of existing producers in the PT. Pacific Television Manado. The issue of this research is limited to 4 pillars of Balance Scorecard. The result of this research shows that on the financial perspective evaluation, producer ability in preparing or sets the production budget has been going well. Producer performance assessed from the customer perspective is quite good where the producer has been able to describe audience want or taste in visual form. In internal business process perspective, the producer has been going well. From the learning and growth perspective, the contributions made by the producer judged to have pretty good where both of productivity, satisfaction, skills, knowledge of the customer, internal processes and financial processes and motivating ability of producers have pretty well and in line with corporate objectives. Keywords: producer performance analysis, balanced scorecard